PERBANDINGAN PRINCIPAL AXIS FACTORING DAN MAXIMUM LIKELIHOOD DALAM MENENTUKAN FAKTOR DOMINAN YANG MEMPENGARUHI PEMBELAJARAN NAHWU SHOROF (STUDI KASUS PONDOK PESANTREN ROUDLOTUL MUTA’ALLIMIN PUTRI) - Khusna, Tanwirotul; Akbarita, Rachmadania; Narendra, Risang (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
This study discusses the dominant factors that influence the success of learning nahwu shorof at the Roudlotul Mutaalimin Islamic Boarding School for the daughter of Minggirsari Village. Determining the dominant factor is done to maximize the quality of education in the boarding school, so that the interest of prospective students is increasing. In this study, two extraction methods were compared, namely the Principal Axis Factoring and Maximum Likelihood methods. There are 13 variables that affect the success of nahwu shorof learning, namely the natural environment (P1), social environment (P23), curriculum (P49), madrasa program (P1012), facilities and facilities (P1315), teaching staff (P1619), condition of physiological (P2021), condition of the five senses (P22), interest in learning (P2325), intelligence of students (P26), student talent (P27), motivation of students (P28), cognitive ability (P2930). The purpose of this study, namely to determine the most appropriate extraction method used in the analysis. The result of this study is the Maximum Likelihood method which is more appropriate than the Principal Axis Factoring method, because it has a smaller RMSE (Root Mean Squared Error) value.